Regional programme of action for the women of Latin America and the Caribbean 1995-2001 (ECLAC SantiagoCL, 1994)
Reflects the changes observed in the region and their impact on women. Sets forth a basic package of priority activities for Latin America and the Caribbean that can be carried out in the next five years.
DC